(untitled) (Swiss Medical Weekly, 2018)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a potentially fatal disease, which may occur as a rare complication after acute pulmonary embolism, although the exact epidemiology of CTEPH is unknown. The mechanisms involved in nonresolution of thrombotic material and scarring of large and/or small pulmonary arteries are unknown; some risk factors have been identified. To date, CTEPH is still underdiagnosed and undertreated. The cardinal symptom of CTEPH is dyspnoea on exertion, but diagnosis is challenging owing to nonspecific symptoms. Right heart catheterisation is mandatory for the diagnosis of pulmonary hypertension, followed by several imaging methods including besides ventilation/perfusion scan, computed tomography pulmonary angiography and conventional angiography. Operability assessment by a multidisciplinary team is crucial for the management in all CTEPH patients, as pulmonary endarterectomy (PEA) remains the only curative treatment of choice. PEA leads to substantial improvement of haemodynamics, symptoms, and life expectancy enabling many patients to lead unrestricted lives under sole anticoagulation therapy. For inoperable patients or those with disease not amenable to surgery, medical therapy or balloon angioplasty are emerging treatment options. Owing to the complexity of CTEPH, the diagnosis and treatment of CTEPH patients is reserved exclusively to experienced CTEPH centres.